The Investigation of Communication Skills of Students at Different Departments at a State University in Turkey - ALTUN, Meryem; KÜRTÜL, Necmettin; SOYCAN, Merve (International Journal of Scientific Research and Management (IJSRM), 2018)
The main purpose of this study was to investigate communication skills of students studying at different departments at a state university. The survey model was used in the study. The data were collected by the Effective Communication Skills Scale developed by Buluş et al., (2017).The sample of the study consists of 277 university students studying in different departments.  According to the results of the research; it was found that there was a significant difference between gender variable and active participative listening and empathy subscale. Moreover, it was seen that this difference was in favor of women in both sub-scales. Considering the differences in terms of groups, it was found that the difference was determined among the departments of coaching, art, music and Teaching Physical Education and Sports, which was in favor of the department of coaching. In the literature, the communication skills could be higher in departments of art, music and Teaching Physical Education and Sports. The results obtained in the current study were contradictory to the above mentioned statement. It can be concluded that during the coaching practices, the coaches interact with sportsmen and other individuals as well as the courses they take during their education are the reasons why they have high communication skills than other departments.